A Pilot Feasibility Study of Interpersonal Psychotherapy for the Prevention of Excess Weight Gain Among Adolescent Military-dependent Girls. Issue 3 (26th February 2021) - Pine, Abigail E; Schvey, Natasha A; Shank, Lisa M; Burke, Natasha L; Neyland, M K Higgins; Hennigan, Kathrin; Young, Jami F; Wilfley, Denise E; Klein, David A; Jorgensen, Sarah; Seehusen, Dean; Hutchinson, Jeffrey; et al.
ABSTRACT: Introduction: Adolescent military-dependents face unique psychosocial stressors due to their parents' careers, suggesting they may be particularly vulnerable to excess weight gain and symptoms of depression and anxiety. Despite these risk factors, there is a lack of tested preventative interventions for these youths. Given the transient nature of military family deployments, research may be hindered due to difficulty in collecting long-term prospective outcome data, particularly measured height and weight. The primary aim of this study was to examine the feasibility and acceptability of collecting body mass index (BMI, kg/m 2 ) outcome data up to 2 years following a randomized controlled pilot trial of an adapted interpersonal psychotherapy (IPT) program aimed at preventing excess weight gain and improving psychological functioning for adolescent military-dependents. In exploratory analyses, patterns in body composition over time were examined. Materials and Methods: Twenty-seven adolescent military-dependent girls (baseline: M age : 14.4 ± 1.6 years; M BMI : 30.7 ± 4.9 kg/m 2 ; M BMI- z : 1.9 ± 0.4) participated in this study. After a baseline assessment, utilizing a computerized program to create a randomization string, girls were assigned to either an IPT or a health education (HE) program. Participants completed three follow-up visits (posttreatment, 1-year follow-up, and 2-year follow-up). Girls completed a Treatment Acceptability Questionnaire at posttreatment; at all time points, height and fasting weight were collected. For the primary aim, Fisher's exact tests examined the rate of obtained follow-up data and lost to follow-up status between the two groups, Mann-Whitney U tests examined the session attendance between groups, and treatment acceptability ratings were compared between the two groups at posttreatment using an independent samples t -test. For the exploratory aim, one-way analyses of covariance (ANCOVAs) examined the group differences in BMI at each time point, adjusting for baseline values, and paired samples t- tests examined the within-group differences at each time point relative to baseline. Using imputed data in the full intent-to-treat sample, mixed model ANCOVAs were conducted to examine the group differences over time. Results: Across both groups, girls attended an average of 72.0% of sessions. At least partial data were collected at posttreatment, 1-year follow-up, and 2-year follow-up for 96.3%, 85.2%, and 74.1% of the participants, respectively. There were no significant group differences in follow-up data collection rates, follow-up status, number of sessions attended, or treatment acceptability. BMI -z stabilized across groups, and there were no group differences in BMI- z . In adjusted ANCOVA models with imputed data, no significant group-by-time effects emerged. Conclusions: For this randomized controlled prevention trial, long-term outcome data collection of measured BMI was possible in adolescent military-dependents and IPT was an acceptable and feasible intervention. An adequately powered trial is required to assess the efficacy of this intervention among military-dependents for obesity prevention and improvements in BMI.